Evidence for High Rates of Gas Transport in the Deep Subsurface. Issue 7 (1st April 2019) - Stauffer, P. H.; Rahn, T.; Ortiz, J. P.; Salazar, L. J.; Boukhalfa, H.; Behar, H. R.; Snyder, E. E.
Abstract: Barometric pumping caused by atmospheric pressure fluctuations contributes to the motion of gases in the vadose zone. While the resulting gas transport is often negligible in unfractured porous rocks, rates of transport in fractured media can be significant. Deep atmospheric pumping has implications for nuclear gas detection, water balance, and contaminant transport. We present results from a tracer test conducted to characterize deep subsurface fractured basalt and investigate the effects of barometric pumping on gaseous contaminant mobility. The tracer test provides data to constrain permeability, porosity, and diffusivity in a numerical representation of the experiment. A numerical model is used to simulate gas flow and dispersive transport under fluctuating pressure conditions. Tracer test and simulation results suggest that barometric pumping induces 10 to 100 times more mixing in the basalt than predicted by gas diffusion alone. Within the basalt fractures, estimates of gas velocity reach maximums of nearly 1, 000 m/day. Plain Language Summary: Weather systems have associated changes in atmospheric pressure. Storm systems bring low pressure and blue skies bring high pressure. These changes in pressure are also imposed on the soils and rocks beneath our feet. If the soils and rocks have sufficient open pore space or well‐connected fractures, atmospheric pressure changes can drive air into or pull air out of these geologic materials. This phenomenon is known as barometric pumping. Barometric pumping can accelerate the migration of natural or man‐made gases. In this study, we have investigated the effects of barometric pumping on a highly fractured geologic formation that underlies the Los Alamos National Laboratory. To do so, we injected a nonreactive tracer gas called sulfur hexafluoride and monitored its concentration over time for several days. These measurements are used to constrain simulations that take into account the fractured nature of the geologic formation. We have determined that barometric pumping has a significant influence on this particular geologic formation and discovered that gases may travel at rates of up to a kilometer per day for brief periods, much higher than the tens of centimeters per day possible if the gases were dispersed by simple molecular diffusion. Key Points: Barometric pumping can induce significant gas flow and transport in deep fractured media Tracer testing helps characterize subsurface permeability, porosity, and diffusivity Simulations elucidate barometrically induced spreading of gas constituents in fractured rock and can aid in predictions of gas releases